Graded Eccentric Rehabilitation After Adipose-Derived Stem Cell Injection for Knee Osteoarthritis: A Systematic Review - Faulina Yosia Panjaitan; Himawan Widyatmiko; Farkhana Dwi Ariyani; Aisyah Muthia Rasyida (Medicinus, 2026)
Background: Knee osteoarthritis is a leading cause of disability worldwide, and adipose-derived cell therapies have emerged as potential disease-modifying interventions. However, no direct evidence exists for graded eccentric rehabilitation following adipose-derived cell injection. This systematic review synthesized the indirect clinical evidence from adipose-derived mesenchymal stem cell, stromal vascular fraction, and microfragmented adipose tissue injection trials for knee osteoarthritis to characterize post-injection rehabilitation practices, efficacy, and safety. Methods: PubMed, EMBASE, and Scopus were searched from inception through 15 May 2026. Eligible studies were human clinical trials of intra-articular adipose-derived cell or stromal vascular fraction injection for knee osteoarthritis reporting pain, function, imaging, or safety outcomes. Study selection was performed independently by all authors, with discrepancies resolved through discussion. Risk of bias was assessed using the Cochrane Risk of Bias 2 tool for randomized trials and the Risk of Bias in Non-Randomized Studies of Interventions tool for observational studies. Result: Eighteen studies (811 participants) were included. No study directly examined graded eccentric rehabilitation after adipose-derived cell injection. Post-injection protocols ranged from simple rest to conventional physiotherapy. Most randomized controlled trials demonstrated significant improvements in pain and function scores, with favorable safety profiles. Risk of bias ranged from low-to-some concerns in placebo-controlled trials to serious in uncontrolled cohort studies. Conclusions: Adipose-derived cell therapies for knee osteoarthritis demonstrate promising short-to-medium-term clinical benefits with acceptable safety. However, the complete absence of graded eccentric rehabilitation protocols in the existing literature represents a critical evidence gap warranting future investigation.